Modularization of iOS applications - Gomes, Matheus Francisco da Silva Lima (2023)
The need for companies to deliver modern, fast, and functional applications is increasingly latent in the technology market, due to the large public that has mobile devices. The development process has undergone significant changes due to issues related to technological development and the widespread adoption of technology in the daily lives of people around the world. As a result of these advances, important issues have arisen to increase the productivity of teams and improve the maintainability of systems, such as controlling the space that applications occupy on user devices, the architecture of applications for mobile devices, and dependency injection, among other important topics for the platform. This article aimed at bibliographical research to cite common challenges to establishing the constitution of modular applications, enabling the modernization, maintainability, and fast and consistent deliveries for companies that need a scalable application, it listed key points to produce applications with emphasis on the iOS operating system. Contributing to the technology community on this subject, where there is little literature on application architecture.